Cuidados paliativos: comunicação entre enfermeiro e paciente terminal - Andrade, Cristiani Garrido de (2013)
INTRODUCTION: The palliative care comprehends a holistic approach of assistance for patients without cure possibilities and their families, in order to provide them a better quality of life. Its application is greatly relevant, in the ambit of care directed to terminal patient. OBJECTIVES: This is study aims to investigate the comprehension of assistance nurses regarding palliative care; to identify the strategies that nurses use to promote palliative care for terminal patient; to ascertain how nurses utilize communication, in the ambit of palliative care, when assisting the patient in terminal phase, to investigate how nurses use the communication to broach the bad news for patient in terminal phase and their family in the practice of palliative care. METHODOLOGY: This is an exploratory research of qualitative nature in which the investigate scenario was a public health institution, located in the city of João Pessoa PB; participated in the research twenty eight assistance nurses. For data collection, that occurred between August and October 2012, was utilized a form containing pertinent question to the proposed objectives for the research. As registry unit for the analysis of empirical material, it was chosen the thematic content analysis, from the following phase: pre-analysis, material exploration and treatment of results, inference and interpretation. The data obtained by means of discourse expressed by the participants of the investigation were grouped in the following thematic categories: Palliative care: conceptual aspects and care strategies with the patient in terminal phase, with their respective subcategories: Palliative care promotion of life quality for patients without possibilities of cure; strategies utilized for the promotion of palliative care directed for the patient in terminal phase and Palliative care and Communication, with the subcategories: Palliative care and communication interpersonal relation of the nurse with the terminal patient, communication of difficult news support for patients and families under palliative care. RESULTS: The research included from the vision of the involved professionals, the valuation of palliative care considered as a modality of care which aims to minimize the suffering of the patient without therapeutic possibilities of cure/terminal and of their family, by means of an assistance guided by humanization. Results evidenced that nurses utilize useful and appropriate strategies that meet the needs of patients and their families, in the context of the addressed care all over its dimension, with emphasis on verbal and nonverbal communication, as essential part of care with the patient and the family. FINAL CONSIDERATIONS: We consider that this study opens a new horizon, in the field of care, of teaching and learning in Nursing, with emphasis in the importance of palliative care and of the communication with the patient in terminal phase. Because of the reduced quantum, of studies directed to this thematic, in the ambit of national literature, it is hoped that this research can subsidize new investigation that contemplate the interrelation of Palliative care with the communication.